The Potential of Mixed Tea from Mangosteen Pericarp, Clove, And Cinnamon in The Functional Scope of Creating a Healthy Liver Organ - Yunita Satya Pratiwi; Yusinta Aristina Sanjaya; Rosida; Ratna Yulistiani; Ulya Sarofa; Anggun Pratiwi Rohimatul Inziyah; Nadien Mutia Intan Maulidi; Ufairah Fithriyati (Nusantara Science and Technology Proceedings, 2024)
The liver, which is the largest organ in the intestinal tract can do several very complex jobs. The use of herbal teas that utilize plants with high antioxidant content is one strategy that is starting to attract interest. In tea form, a blend of mangosteen pericarp, cloves, and cinnamon can protect the liver from oxidative damage and inflammation. The purpose of this article is to explore, analyze, and summarize various theories about the potential of a mixture of mangosteen, cinnamon, and clove tea, hepatoprotective mechanisms, and liver health biomarkers in terms of antioxidant content. The writing method used is a literature review from international and national journals by tracing and summarizing several theories related to the topic and title of the article to be written, which ultimately develops new conclusions as broader and stronger theories. The results show that mangosteen peel, cloves and cinnamon have functional benefits, namely they can create a healthy liver because of their antioxidant content. Mangosteen peel contains quite high polyphenol antioxidants, including xanthones, phenolic acids, flavonoids, catechins, hexadecanoic acid, and oleic acid. Cloves contain the antioxidants eugenol, saponins, tannins, flavonoids, and polyphenols. Cinnamon contains phenolic antioxidants such as eugenol, cinamic aldehyde and beta caryo-phyllene Damage to cell membranes and proteins is a sign of oxidative stress caused by free radicals. Therefore, antioxidants are needed to convert free radicals into non-reactive compounds. Biomarkers of a healthy or damaged liver are through blood tests including levels of SGPT, SGOT, SGPT-SGOT, Gamma GT, albumin and globulin levels, bile acid levels, and bilirubin levels. In conclusion, tea mixed with mangosteen peel, cloves, and cinnamon contains high levels of antioxidants so it has the potential to protect against liver damage due to various oxidative stress factors.